PENAMBAHAN DAN VARIASI DIMENSI SIRIP ALUMINIUM PADA TUBE TERHADAP LAJU DAN EFEKTIVITAS PERPINDAHAN PANAS DALAM HEAT EXCHANGER TIPE SHELL AND TUBE - T., Rohman; Sutjahjono, Hary; Listyadi, Digdo (ROTOR, 2013)
Heat exchanger is a device that serves to change temperature and the phase of fluid. By utilizing heat transfer between two fluids with different temperature from the higher temperature fluid to a lower temperature fluid. This study aims to determine the effect of the addition aluminum fins and dimensional variations on the effectiveness shell and tube heat exchanger. Heat Exchanger was tested by varying the dimensions of the aluminum fins on the tube from the tube without fins, fin tube with a length of 10 mm, 20 mm, and 30 mm. Tests carried out in counter flow so that the heat transfer rate will be better than the directional flow. Of the test will come out hot fluid temperature and cold fluid temperature out. The results showed decreases in the rate of heat transfer fins greater dimension and the dimension of the highest effectiveness without fins. The highest effectiveness is 25.85% in tube without fins. It can be concluded that the addition of fin in this research will reduce the effectiveness of the heat exchanger shell and tube type.Â Keywords: Aluminum, effectiveness, fin dimension, heat exchanger